PENGARUH REALISASI PENERIMAAN PAJAK HOTEL, PAJAK RESTORAN DAN PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH (BPPRD) KOTA BANDAR LAMPUNG - Pertiwi, Nur Aulia (Jurnal Enterpreneur dan Bisnis (JEBI), 2023)
Regional Original Income is obtained from various sources of income, one of which is sourced from local tax collection. There are several sectors that contribute to Regional Original Income (PAD), including Hotel Tax, Restaurant Tax and Advertising Tax. This study aims to determine the effect of the tax revenue on the Regional Original Income (PAD) of Bandar Lampung City. This study uses a quantitative method by processing data obtained from the Regional Tax and Levy Management Agency of Bandar Lampung City. The sample in this study is the amount of Hotel Tax, Restaurant Tax and Advertising Tax receipts for Bandar Lampung City from 2017 to 2021 (data per month) as many as 60 samples. The analysis in this study is multiple linear regression analysis, classical assumption test, and hypothesis testing with a significance level of 5%. The results of the calculation of the F test, the value of Fcount is 12.313 Ftable 2.76, meaning that Ho is rejected and Ha is accepted. So it can be concluded that the independent variable (Independent) which consists of Hotel Tax (X1), Restaurant Tax (X2) and Advertising Tax (X3) has a simultaneous effect on the dependent variable (Dependent) which consists of Regional Original Income (Y) at the Management Agency. Regional Taxes and Levies Bandar Lampung City. Based on the results of this study shows the results of multiple regression Y = 14,730245280,646 + 4,858X1 + 1,025X2 + 1,720X3 + e. The results of the study obtained a correlation coefficient (R) of (0.397). The coefficient of determination R² is (0.365). This means that the independent variable consisting of Hotel Tax, Restaurant Tax and Advertising Tax affects the dependent variable of Local Original Income by 39.7% while the remaining 60.3% is influenced by other variables